Isotopes of the Earth's Hydrosphere - Ferronsky, V.I.; Polyakov, V.A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
This book covers the distribution, hydrochemistry and geophysics of the naturally occurring stable isotopes namely:  hydrogen, oxygen and radioactive tritium, carbon and other cosmogenic and radiogenic isotopes of the uranium-thorium series, in the oceans and in atmosphere, the earth's surface and ground water. The use of environmental isotopes in the three main areas of natural waters is discussed: origin, dynamics and residence time in natural reservoirs. The origin of the hydrosphere is examined in the light of isotopic, new cosmochemical and recent theoretical results. The book will be of interest to scientists and researchers who use environmental isotopes in solving scientific and practical problems in hydrology, hydrogeology, oceanography, meteorology, hydrogeochemistry and cosmochemistry. Lecturers, students and postgraduates in these fields will also find it useful.
Part I Stable Isotopes -- Isotope geochemistry of natural waters -- Isotopic composition of ocean water -- Isotopic composition of atmospheric moisture -- Isotopic composition of surface continental water -- Isotopic composition of water of the unsaturated and saturated zones -- Isotopic composition of formation water.-  Hydrogen and oxygen isotopic composition of sedimentary rocks and implications for palaeothermometry -- Hydrogen and oxygen isotopic composition of groundwater in volcanic regions -- Hydrogen and oxygen isotopic composition in minerals of magmatic and metamorphic rocks and fluid inclusions -- Other stable isotopes in the hydrosphere -- Part II Cosmogenic Isotopes -- Origin and production of cosmogenic isotopes -- The distribution of tritium -- The distribution of radiocarbon -- The other cosmogenic isotopes in natural waters -- Part III Radiogenic Isotopes -- Production and distribution of radiogenic isotopes -- Dating of groundwater and sediments -- Part IV Applications -- Applications to the problems of dynamics of natural waters -- Palaeohydrology of the Aral-Caspian basin -- The nature and mechanism of the Earth shell separation and origin of the hydrosphere.
Keywords: Geochemistry; Hydrology; Hydrogeology; Environmental sciences; Geochemistry; Hydrology/Water Resources; Hydrogeology; Environmental Science and Engineering